Developing language and literacy with young children - Whitehead, Marian R. (London : Sage publication, 2011)
Looking at the important aspect of human development - communication and language in the early years - this book gives carers, parents, teachers and other professionals who work and play with young children an understanding of children's communication and language development in the years from birth to age eight
Includes bibliography and index.
Keywords: Language arts (Early childhood).; Literacy; Children -- Language